2018
DOI: 10.3390/c4040068
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Carbon Materials Explored by Local Transmission Electron Microscopy and Global Powder Diffraction Probes

Abstract: Transmission electron microscopy and neutron or X-ray diffraction are powerful techniques available today for characterization of the structure of various carbon materials at nano and atomic levels. They provide complementary information but each one has advantages and limitations. Powder X-ray or neutron diffraction measurements provide structural information representative for the whole volume of a material under probe but features of singular nano-objects cannot be identified. Transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 156 publications
(284 reference statements)
5
54
0
1
Order By: Relevance
“…As previously discussed, a BSU domain can be thought as made of a stack of few and small graphene fragments. In addition to flat graphene domains, curved graphene layers are present [19]. Recent HRTEM studies on soot confirmed the presence of curved graphene domains resembling those of fullerene [20].…”
Section: Particle Structure and Modificationmentioning
confidence: 99%
“…As previously discussed, a BSU domain can be thought as made of a stack of few and small graphene fragments. In addition to flat graphene domains, curved graphene layers are present [19]. Recent HRTEM studies on soot confirmed the presence of curved graphene domains resembling those of fullerene [20].…”
Section: Particle Structure and Modificationmentioning
confidence: 99%
“…The broad peak centered near 23 corresponded to the (002) planes in amorphous graphitic carbon, and it along with the peak at 49.32 were characteristic of GO in biomass. 29,34,[49][50][51] The diffraction pattern of the PAN nanober mat (CNF0) contained a sharp peak at 17 , which corresponded to the (010) planes in crystalline PAN. 47 A sharp peak appears near 28 in the XRD pattern of pure PAN.…”
Section: Xrd Analysismentioning
confidence: 99%
“…D-spacing (d 002 ) and axial size of carbon crystallite (L c ) were calculated based on characteristic (002) carbon peak around 25 • . The Bragg angle of the (002) peak was used to calculate D-spacing, and L c was calculated based on the Debye-Scherrer equation using the full width at half maximum (FWHM) value of the peak [29,33]. While the D-spacing of Super-P was slightly smaller than that of PE-derived carbon, L c was much bigger than that of PE carbon, indicating superior carbon structural development of Super-P in the axial direction.…”
Section: Resultsmentioning
confidence: 99%